Removal of Cr(VI) by continuous flow electrocoagulation reactor at controlled and uncontrolled initial pH conditions - Akhtar, Nawid Ahmad; Kobya, Mehmet; Khataee, Alireza (Elsevier, 2025)
In this work, we studied the impact of various operating parameters, including reaction time (t), applied current (i), charge loading (q), initial pH, initial Cr concentration (mg/L), and wastewater flow rate (Q), on the removal of Cr (VI) from synthetic tap water. The investigation is conducted using Fe scrap anodes in a continuous flow electrocoagulation process (CFEC) with both controlled and uncontrolled initial pH conditions. Cr(VI) removal efficiency under controlled pH conditions was found to be 100 % under optimum conditions (t = 6 min, i = 1 A, pH = 2.5, q = 6.67 C/L or 4.145 F/m3, Q = 15 mL/min, and Ci = 90 mg/L). In the case of uncontrolled pH conditions at optimum conditions (t = 12 min, i = 1 A, pH = 2.5, q = 13.33 C/L or 8.29 F/m3, Q = 15 mL/min, and Ci = 90 mg/L), the Cr(VI) removal efficiency was found to be 100 %. The Cr(VI) removal capacity and the iron to chromium molar ratio at controlled pH were 775 mg Cr/g Fe and 1.198 mol/mol, and at uncontrolled pH were 387.7 mg Cr/g Fe and 2.395 mol/mol, respectively. Finally, comprehensive investigations were carried out on specific energy consumption and total operating costs. The SEM results show that the sludge particles under controlled and uncontrolled pHs are irregular, characterized by amorphous structure and wrinkled surfaces with small agglomerations.
Keywords: Cr(VI) removal; Continuous flow electrocoagulation reactor; Fe scrap anode; Charge loading; Operating cost